Problems of Inclusive Education in the Field of Physical Culture in Technical University - V. Pryakhin, S. (International Journal of Engineering and Technology, 2018)
At all phases of formation of a motor skill, the formation of both neuromuscular and vegetative components takes place. At the same time, vegetative reactions are becoming more specific and reflect requests from the motor sphere. The present article discusses the formation of a sequence of mental action programs, allowing to improve the quality of inclusive education in the field of physical culture at the university.Â